A Review of the Ethnomedicinal, Phytochemical, and Anticancer Properties of Melicope Species - Idris, Adewale Ahmed; Md. Sanower, Hossain; Lim, Pei Cee; Nor Hisam, Zamakshshari (John Wiley & Sons, Inc, 2023)
The genus Melicope, which consists of 230 species, stands out as the largest genus within the Rutaceae family. Melicope species are characterized by their evergreen nature and can range from shrubs to predominantly dioecious trees. The Melicope species have been utilized in traditional medicine to address a wide range of ailments, including fever, colds, cramps, and inflammation. These plants have gained significant attention due to their noteworthy ethnopharmacological and ethnomedicinal significance. Researchers have isolated numerous biologically active secondary metabolites from different Melicope species, which include polymethoxylated flavonoids, furanocoumarins, acetophenones, benzenoids, and quinolone alkaloids. These compounds exhibit diverse biological activities, such as antibacterial, antidiabetic, antifungal, and antiproliferative properties against human cancer cell lines. This review provides an update on the chemical constituents of the selected species of Melicope. The study also highlights the anticancer and cytotoxicity properties of the plant extracts and phytochemical constituents from Melicope species. Furthermore, the molecular mechanisms underlying the anticancer effects are elucidated. Overall, this review contributes to understanding the significant pharmacological potential of Melicope species and unlocking their chemical composition, emphasizing their relevance in the development of therapeutic agents, particularly in the field of cancer research.